Development and Evaluation of Grape Seed Oil Body Butter: Skin Nourishment and Moisture Retention - Md. Usman, Md. Rageeb; D. Patil, Gitanjali; D. More, Nalini (Journal of Neonatal Surgery, 2025)
This study delves into the development and analysis of body butter enriched with grape seed oil, celebrated for its rich linoleic acid content and powerful antioxidants. The primary goal is to create a skincare product that enhances hydration, supports skin repair, and exhibits anti-inflammatory properties. By incorporating grape seed oil alongside other natural components, the formulation emphasizes improved functionality and sensory qualities, such as texture and spreadability. The research further involves comprehensive assessments of its physical and chemical properties, stability over time, and compatibility with the skin, showcasing its potential as an effective and versatile option for everyday skincare.